The Impact of COVID-19 on Thailands Public Health Emergency Management System: A Case Study - Suwanna Bengthong; Preecha Suvarnathong; Suwimon Ukraisa; Kanchana Boonphak; Rungrueng Kitphati; Juraporn Krates; Wilailuk Ruangrattanatrai; Worayuth Nak-Ai (My University, 2024)
Purpose: This phenomenological qualitative research investigates Public Health Emergency Management (PHEM) in response to COVID-19, with a specific focus on the case of Thailand’s Health Region 9 (Nakhon Ratchasima) and its program known as COVID-19 Back Home. Method: The study gathers data through in-depth interviews with four groups comprising a total of 112 individuals from three Thai provinces. The collected data is subjected to content analysis, and the findings are analyzed using a framework based on system theory. Results and conclusion: The successful management of subjects returning home is highlighted, resulting in saving numerous patients' lives. The study identifies various suggestions and success factors for each phase of the management process. The research sheds light on PHEM situations in response to COVID-19, specifically examining Health Region 9's COVID-19 Back Home program. Implications of the research: The study provides valuable insights into the inputs, activities, and processes involved in managing such situations, showcasing successful strategies, collaborative efforts, and behavioral changes. Originality/value: The identified suggestions and success factors can inform and improve future management approaches.
Keywords: 2019-20 coronavirus outbreak; Pandemic; COVID-19 Pandemic Impacts